The biology of Endophyllum osteospermi, and its use for the biological control of Chrysanthemoides monilifera ssp. monilifera - Wood, A. R. (Alan Robert) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD Agric)--University of Stellenbosch, 2004.